2005
DOI: 10.1021/ja050477g
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Hydration of Ionized Aromatics. Energies, Structures of the Hydrated Benzene Cation, and the Mechanism of Deprotonation Reactions

Abstract: The stepwise binding energies (DeltaHdegree(n-1,n)) of 1-8 water molecules to benzene(.+) [Bz(.+)(H2O)n] were determined by equilibrium measurements using an ion mobility cell. The stepwise hydration energies, DeltaHdegree(n-1,n), are nearly constant at 8.5 +/- 1 kcal mol-1 from n = 1-6. Calculations show that in the n = 1-4 clusters, the benzene(.+) ion retains over 90% of the charge, and it is extremely solvated, that is, hydrogen bonded to an (H2O)n cluster. The binding energies and entropies are larger in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
121
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(134 citation statements)
references
References 44 publications
13
121
0
Order By: Relevance
“…Further insight into the deprotonation of benzene photoions, at the molecular level, can be had from a recent, in-depth study of the hydration of ionized aromatics [16]. This study provides details of the mechanism through which water, with an even lower GB (660 kJ mol…”
Section: Hypothesis Regarding Substituent Effects On Proton Transfer mentioning
confidence: 99%
See 1 more Smart Citation
“…Further insight into the deprotonation of benzene photoions, at the molecular level, can be had from a recent, in-depth study of the hydration of ionized aromatics [16]. This study provides details of the mechanism through which water, with an even lower GB (660 kJ mol…”
Section: Hypothesis Regarding Substituent Effects On Proton Transfer mentioning
confidence: 99%
“…. O ␦Ϫ bond (see Figure 4 in reference [16]). Note that the positive charge on C 6 H 6 ϩ• is distributed among its hydrogens, even though the missing electron is from a ring -orbital.…”
mentioning
confidence: 99%
“…For large clusters (n ≥ 4) IR spectra of the clusters suggest features that are nearly identical to protonated water clusters, suggesting exclusion of benzene and the formation of an attached water cluster. For smaller clusters (n ≤ 3), IR spectra were shown to be consistent with a hydrated benzene cation, where benzene retains over 90 % of the charge (Ibrahim et al, 2005). It is likely that the sensitivity dependence we observe in these experiments is related to the aforementioned laboratory studies and depends on the location of the charge (benzene vs. water) and the size of the benzenewater cluster (n), both of which are related to q.…”
Section: Impact Of Ambient Humidity On Sensitivitymentioning
confidence: 52%
“…Expected contributions from carbon-13 isotopes were accounted for in the calculated proton transfer products. Ibrahim et al (2005) show that the stepwise binding energies for attaching a water molecule to C 6 H + 6 are on the order of 8.5 kcal mol −1 , suggesting that the water molecules are removed via collisions in the transfer optics. Laboratory studies have shown previously that benzene-water clusters [C 6 H 6 -(H 2 O) n ] + can be made efficiently (n = 1-23) (Miyazaki et al, 2004).…”
Section: Impact Of Ambient Humidity On Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation